Pemanfaatan Tiktok Sebagai Media Dakwah - Hudaya, Abdul Hasib; Muhlis, Atjep; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The purpose of the research is to understand the process of preaching found on the TikTok account @Yudhidarmawan, how TikTok is utilized as a preaching medium by Yudhi Darmawan, and what the supporting and inhibiting factors are for preaching through the TikTok social media platform.This research uses a qualitative approach with the Technology Determinism theory by McLuhan.This research shows that the da’wah process carried out by Yudhi Darmawan as a da’wah actor involves conveying da’wah messages in the form of daily life problems through short videos.Yudhi Darmawan uses various strategies and methods to utilize the TikTok application as a medium for preaching, leading to the conclusion that preaching through TikTok has many supporting factors but is not without several hindering factors in its implementation.